2020
DOI: 10.6018/eglobal.370021
|View full text |Cite
|
Sign up to set email alerts
|

Adicción a la comida y estado nutricional en adolescentes de una preparatoria pública en México

Abstract: Objetivos: Conocer la prevalencia de la adicción a la comida de acuerdo a la edad, sexo e índice de masa corporal, y determinar la asociación entre la adicción a la comida y el estado nutricional en adolescentes del norte de México. Método: Estudio descriptivo correlacional de corte transversal, realizado durante agosto y septiembre de 2018. La población se conformó por 630 adolescentes estudiantes de 15 a 17 años de edad, de una preparatoria pública en Nuevo León, México, a los que se les realizaron medicione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
4
4
0
2
Order By: Relevance
“…In this sense, recent research [67] reveals the relevance of promoting good dietary habits from all the areas of development of the adolescent, i.e., family, school and community on account of the consequences that this has for their health in the short and long term. Current research studies [63,68] into different contexts point out the important role that this early nutritional education has in the emergence of eating disorders in adolescents, as well as the need to draw up strategies and protocols of action once these appear. What is most relevant from the point of view of this scenario is that the findings deriving from this study enable us to contribute to the completion of studies on personality patterns and other psychologic variables, which are the result of habits learned in development stages previous to adulthood, and the chronification of which is highly resilient to intervention [61].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, recent research [67] reveals the relevance of promoting good dietary habits from all the areas of development of the adolescent, i.e., family, school and community on account of the consequences that this has for their health in the short and long term. Current research studies [63,68] into different contexts point out the important role that this early nutritional education has in the emergence of eating disorders in adolescents, as well as the need to draw up strategies and protocols of action once these appear. What is most relevant from the point of view of this scenario is that the findings deriving from this study enable us to contribute to the completion of studies on personality patterns and other psychologic variables, which are the result of habits learned in development stages previous to adulthood, and the chronification of which is highly resilient to intervention [61].…”
Section: Discussionmentioning
confidence: 99%
“…There were minimal differences however between health professionals based on whether they work with infants, children and adolescents, adults, or across the lifespan. This lack of difference is interesting, given that studies have demonstrated the severity of addictive eating is often greater with increased age [15][16][17]. This might have meant greater agreement among those working with adults; however, the lack of difference could be due to the small proportion of the sample who work with infants, children and/or adolescents only in this study (11%) or given the period of adolescence and the wide variety of changes that occur or are reported at this age.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha identificado que, a menor edad, mayor control del peso, pues conforme incrementan los años, la masa grasa corporal incrementa y la masa magra disminuye (Avsar et al, 2017;Mazurek Melnyk et al, 2015). El sexo que predomina en el sobrepeso y obesidad es la mujer (Devaux & Vuik, 2019;Guevara Valtier et al, 2020;Instituto Nacional de Estadística y Geografía, 2017;Rangel Caballero et al, 2015;Sinclair et al, 2016).…”
Section: Factores Personalesunclassified
“…El primero, provoca sentimientos positivos y de pertenencia en los adolescentes (Holmberg et al, 2019). Los mensajes de texto, aplicaciones móviles, correos electrónicos, plataformas tipo Facebook, Instagram o Twitter, el internet y videos de YouTube, promueven la adopción de hábitos saludables, sobre todo cuando se muestra al adolescente como modelo a seguir en su contenido (Chau et al, 2018;Chávez Montes-de Oca et al, 2018;Guevara Valtier et al, 2020;Hunter et al, 2019;Mason et al, 2018). Específicamente, los adolescentes eligen determinada red social en función de lo que pretenden mostrar.…”
Section: Influencias Interpersonalesunclassified